A New Model for Semiautomatic Student Source Code Assessment - Stankov, Emil; Jovanov, Mile; Madevska Bogdanova, Ana; Gusev, Marjan (Journal of computing and information technology, 2013)
Programming courses at university and high school level, and competitions in informatics (programming),often require fast assessment of the received programming tasks solutions. This problem is usually solved by the use of automated systems that check the produced output for some test cases for every solution.